Industrial Revolution 4.0 & academic librarians: where are we now? / Asmadi Mohammed Ghazali ...[et al.] - Mohammed Ghazali, Asmadi; Abdul Rahman, Abd Latif; Othman, Nor Hidayah (Universiti Teknologi MARA, Kedah, 2021)
Competencies that comprised of knowledge, skills and attitudes are widely changing especially in the era of IR4.0. Malaysians nowadays are trying to be parallel with the existence and transformation of sophisticated and challenging technology particularly in academic library's environment. These technologies will help the academic librarians to enhance the library's service for the users' needs. Managing academic librarians is not an easy task a to ensure users can get access to the library's services and materials with comfort and successfully especially in IR4.0 era. This conceptual paper comprises s how academic librarian presenting the knowledge, skills and attitudes in Industrial Revolution 4.0 (IR4.0).